1968
DOI: 10.1002/1097-0142(196808)22:2<345::aid-cncr2820220211>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomatous pseudotumor of lung. A case report with electron microscope and lipid studies

Abstract: A large benign xanthomatous pseudotumor, 10 cm in diameter, was successfully removed from the lung of a 5 1/2‐year‐old girl. The exact nature of this unusual lesion was not known but light and electron microscopy and lipid analyses suggested either a chronic inflammatory lesion in which mast cells were prominent or a benign tumor arising from poorly differentiated neuronal elements in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1972
1972
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…The prognosis of patients who undergo complete resection of endobronchial inflammatory pseudotumors is favorable; 8 however, an inflammatory pseudotumor compressing the mediastinum has been reported. 14 While these tumors may invade the mediastinum, 6,13 diaphragm, 13,15 and chest wall, 16 metastasis has never been reported. Although recurrence after surgical excision is unusual, long-term follow-up is required because recurrence as late as 9-11 years after surgery has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients who undergo complete resection of endobronchial inflammatory pseudotumors is favorable; 8 however, an inflammatory pseudotumor compressing the mediastinum has been reported. 14 While these tumors may invade the mediastinum, 6,13 diaphragm, 13,15 and chest wall, 16 metastasis has never been reported. Although recurrence after surgical excision is unusual, long-term follow-up is required because recurrence as late as 9-11 years after surgery has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The electron microscopical features of seven cases of pulmonary and extrapulmonary plasma cell granulomas have previously been described (Wentworth et al 1968, Kuzela 1975, Buell et al 1976.…”
Section: Discussionmentioning
confidence: 99%
“…Wentworth and his colleagues (Wentworth Lynch, Fallis, Turner, Lowden, and Conen, 1968), described a xanthomatous pseudotumour of the lung in which they found large amounts of phospholipid and cholesterol. They considered that the composition of the lipids was quite unlike that of the xanthomata of the skin and suggested that the lipid may have originated from neuronal elements.…”
Section: Discussionmentioning
confidence: 99%
“…There may however, be examples where the lipid component is so great that the suggested epithelial origin of the lipid is obscured. This group includes the cases of Edwards and Taylor (1938), Scott, Morrow, and Payne (1948), Umiker and Iverson (1954), Titus, Harrison, Clagett, Anderson, and Knaff (1962), Sherwin, Kern, and Jones (1965), Wentworth et al (1968), Dubilier, Bryant, and Danielson (1968), Kaufman, Goldberg, and Tyagi (1968), and Long, Nutt, and MacArthur (1970). These authors make no mention of a papillary element in their cases which is such a feature of the cases of Goorwitch and Madoff (1955), Liebow and Hubbell (1956), Hill and Eggleston (1972), and the present two cases.…”
Section: Discussionmentioning
confidence: 99%